Rozarium Shinjuku, przechadzka. Quasi-dokumentalny portret japońskiej społeczności queer w "Żałobnej paradzie róż" ("Bara no Sōretsu", reż. T. Matsumoto, 1969) - Krauze, Maciej (Zagadnienia Rodzajów Literackich, 2024)
This essay explores the intricate interplay between documentary and narrative elements in the film Funeral Parade of Roses (Bara no Sōretsu, dir. T. Matsumoto, 1969). The film centers on the character of Eddie, a queer individual working as a hostess in a gay bar in Tokyo’s Shinjuku district. The narrative intertwines Eddie’s romantic relationship with the bar owner Gonda and his conflict with the establishment’s manager Leda. Flashbacks to Eddie’s childhood and the revelation that Gonda is his long-lost father have led many Western scholars to interpret the film as a loose adaptation of Oedipus Rex. However, this essay challenges such readings, proposing an analysis of the film through the lens of gender and sexual identity in 1960s Japan. The study integrates elements of Western theory (Ch. Baudelaire, W. Benjamin, G. Deleuze, F. Guattari, S. Sontag) with research on the specificity of Japanese culture (D. Desser, A. Jacoby, M.J. McLelland, A.M. Nornes, D. Richie, T. Satō, T. Schmidt, I. Standish), as well as insights from the director (T. Matsumoto) and his interpreters (M. Ko, M. Raine). The chosen methodology facilitates an exploration of the relationship between the individual and reality as depicted in documentary form. By employing the concept of the flâneur to capture the essence of Shinjuku, the author emphasizes the film’s eclecticism, which, through diverse conventions and cultural influences, creates a nuanced portrayal of Japan’s sexual minorities and offers a commentary on the impact of foreign influences on Japanese collective society.